Hydrothermal Synthesis of CuO Nanoparticles: Tailoring Morphology and Particle Size Variations for Enhanced Properties - Tijen Ennil Bektaş; Uğur Cengiz; Gürkan Akarken (Journal of Advanced Research in Natural and Applied Sciences)
Transition metal oxides, particularly copper oxides, have garnered significant attention due to their intriguing photochemical, photomagnetic, photo-thermal, and photoconductive properties. Among these, CuO stands out as a p-type semiconductor having narrow bandgap energy ranges from 1.2 to 2 eV, finding versatile applications such as gas sensing, magnetic storage, solar energy conversion, photocatalysis, supercapacitors, field-emission emitters, and optical switches. Additionally, it serves as a crucial component in materials designed for lithium-ion electrodes. In this study, five different CuO nanoparticles were synthesized by simple and cost-effective hydrothermal method with various reaction temperatures and times in a teflon lined stainless steel autoclave. Copper (II) chloride dihydrate was used as copper source in this process. Various characterization techniques were conducted including X-ray powder diffraction (XRD), Raman spectroscopy, and transmitting electron microscopy (TEM). The effect of temperature and time on synthesis process was characterized and discussed. TEM images show that particle size of CuO increase with the temperature and reaction time. First reaction had the smallest particle sizes (mostly around 9-11 nm). This can be attributed to its lowest reaction temperature and shortest reaction time. For the other reactions, two of them accumulate around 19-35 nm and two around 27-45 nm range. However, the rise in the particle’s diameters is not directly proportional to temperature and time. As a result, CuO nanoparticles have been produced with simple method for the market. It can be produced in large quantities for heat exchangers, gas sensing, magnetic storage, solar energy conversion, photocatalysts, supercapacitors, etc.